Objectives and Institutions of Regional Development: Interdisciplinary Methodology - Lidia S. Shehovtseva; Pavel P. Chernyshkov (International Journal of Economics and Financial Issues, 2015)
The paper proposes an interdisciplinary methodology for creating goals and development institutions in the region as a subject of the federation. The methodology includes the subject-functional, systemic, organizational and strategic approaches. The study is based on a hypothesis that the potential and actual institutions are the objectives of the main subjects of socio-economic development of the region that define its functions. Meanwhile, the concept and the methodology for determining these objectives can be used for systemic formation of the target institutions. The paper concludes with the methodology of systematization of institutional support for the regional development. Recommendations are given to further systematize the institutional support using the matrix method.